Indonesia-Norway cooperation in reducing emission from deforestation and degradation framework: a case study of Central Kalimantan forest. Issue 1 (October 2020) - Haeda, N; Cangara, A R; Culla, A S; Burhanuddin,; Lumumba, P; Apriliani, A
Abstract: This study aims to describe and explain how Indonesia's cooperation with Norway in the conservation of Indonesia's forests through the REDD+ Framework is related to the interests of both countries in carrying out this environmental cooperation as well as how the implementation of the REDD+ program that both countries have formed for Central Kalimantan's forests. The method used by the writer is a descriptive method of analysis, and data collection techniques used by the author is a literature review. The authors analyzed the data using qualitative analysis techniques supported by quantitative data. The results of this research indicate that the cooperation between Indonesia and Norway certainly has different interests between the two countries. Indonesia itself has the interest to create a good image in the eyes of the international world. It is why Indonesia has a large forest but has various problems. Therefore, it takes a great commitment to maintaining its forests, while on the other hand, Norway has a moral obligation to developing countries that have a large forest. The implementation of the REDD+ program is activities conducted by various stakeholders that developed into the Letter of Intent signed by Indonesia and Norway.